Student Diversity and Fulfillment of Curriculum Targets in SDN Tegal Besar 02 Mathematics Subject Knowing Fractions in Class 2B - Windrayani, Sheila Mei Putri; Ainur, Silvia; Dianawati, Wiwit; Prihandono, Trapsilo; Ningtyas, Ika Fitria (CV. Pusdikra Mitra Jaya, 2025)
Student diversity reflects the diversity of Indonesian society at large, including aspects of language, religion, gender, ethnicity and culture. Environmental differences are one form of diversity that is often found in the world of education. Quality education is education that is able to accommodate and meet the needs of each learner without setting aside the achievement of curriculum targets. Meeting the targets of the mathematics curriculum in the midst of student diversity requires a flexible and responsive learning approach.However, 2B learners face more difficult challenges in the learning process, especially when the learning material becomes more complex one of them is in math learning.The purpose of the study was to improve the learning outcomes of grade 2B students in the material of recognizing fractions in Mathematics subjects by using diverse scaffolding. This class action research method consists of several stages, namely planning, acting, observing, and reflecting. The results after the action is given there is a difference in percentage value, the percentage value of students' completeness is 82.14% and 89.28%. Based on the results have met the KKM value set. This research shows that the application of the project-based learning model in learning fractions can improve the learning outcomes of class 2B students at SDN Tegal Besar 02. In addition, the PjBL model also provides a more enjoyable learning experience and is relevant to everyday life.